"Getting pregnant might make me seem more normal to them": Attitudes, experiences, and gendered nuances regarding pregnancy and parenting among youths experiencing homelessness. Issue 4 (2nd October 2019) - Begun, Stephanie; Torrie, Michaela; Combs, Katie Massey; Frey, Cressida
Abstract: Homelessness among youths exacerbates an array of challenging life experiences, notable examples of which are pregnancy and parenting. Research is lacking on young men's attitudes and experiences, and also the influences which homeless youths' gender identities and sexualities may have on their pregnancy and parenting outcomes and trajectories. This study qualitatively explores gender differentials, including youths' gender identities and sexual orientations, with regard to their attitudes and experiences of pregnancy and parenting while homeless. Qualitative data were obtained from interviews with a diverse sample of 30 female, male, and transgender homeless youths, ages 18 to 21. Findings revealed that topics of pregnancy and parenting represent a wide range of complexities, different standards, and threats for homeless youths. Although pregnancy is often viewed positively within this community, it is received and experienced differently for each gender and sexuality. Results demonstrate that youths' unimpeded access to and knowledge of all available reproductive and sexual health care services is essential. These services must be designed and delivered for youths of all gender identities and sexual orientations. Interventions and resources on parenting and co-parenting, particularly models that more inclusively engage a greater diversity of young parents' involvement, are also urgently needed.